DESKRIPSI KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PEMBELAJARAN DARING PADA MATERI SEGI EMPAT - Perry Zakaria; Nurwan Nurwan; Frendy Dermawan Silalahi (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2021)
This research is a descriptive study that aims to describe students' critical thinking abilities carried out by online learning. This research was conducted in class VIII SMP Negeri Widyakrama involving 23 students as research subjects. Data collection was obtained from validated essay test instruments. The test instrument was used to collect data on students' mathematical critical thinking abilities with indicators (a) problem identification (b) analysis, (c) synthesis, and (d) drawing conclusions. The results showed that students' critical thinking abilities implemented through online learning at Widyakrama State Middle School were in the medium category. This is shown based on the classification of critical thinking abilities of 23 respondents. There are only 5 students who are in the high category, 14 students are in the medium category, and 4 other students are in a low category.